2016
DOI: 10.5301/ijao.5000533
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast–Seeded Bioglass/Gelatin Nanocomposite: A Promising Bone Substitute in Critical-Size Calvarial Defect Repair in Rat

Abstract: We demonstrate the feasibility of engineering a nanocomposite scaffold with an architecture resembling the human bone, and provide proof-of-concept validation for our scaffold using a rat animal model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…Short‐term cell viability and cytotoxicity were measured by MTT (Gholipourmalekabadi et al, ) and LDH‐specific activity assay (Rostami et al, ), respectively. For this purpose, the cells were cultured on the scaffold for 24, 48, and 72 h as described in our previous studies (Johari et al, ; Johari et al, ; Kazemi et al, ) and their proliferation rate was compared with those of the cells cultured in a culture plate (as a positive control). After each period of time, the culture medium was removed and centrifuged for the following cytotoxicity assay with LDH.…”
Section: Methodsmentioning
confidence: 99%
“…Short‐term cell viability and cytotoxicity were measured by MTT (Gholipourmalekabadi et al, ) and LDH‐specific activity assay (Rostami et al, ), respectively. For this purpose, the cells were cultured on the scaffold for 24, 48, and 72 h as described in our previous studies (Johari et al, ; Johari et al, ; Kazemi et al, ) and their proliferation rate was compared with those of the cells cultured in a culture plate (as a positive control). After each period of time, the culture medium was removed and centrifuged for the following cytotoxicity assay with LDH.…”
Section: Methodsmentioning
confidence: 99%
“…In the early 1990s, the first glass obtained by the sol-gel method was developed (Li et al, 1991). and infections (Fooladi, Hosseini, Hafezi, Hosseinnejad, & Nourani, 2013;Johari et al, 2016). We have demonstrated that our BG (BG90) has the marked ability to induce mineral matrix formation A number of studies have stated that BGs should exhibit a macroporous structure, which is optimal for cell growth and vascularization (Johari et al, 2016;Schindeler, McDonald, Bokko, & Little, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…The enhanced bioactivity is due to the enhanced surface area (Sepulveda, Jones, & Hench, ). Accordingly, BGs have accumulated important properties to induce tissue regeneration: (a) the dissolution ions from the glasses behave like growth factors, providing signals to the host progenitor stem cells leading to osteostimulation; (b) promotion of rapid reaction on its surface forming a biologically active hydroxyapatite layer that quickly masks the biomaterial from immune cells; and (c) BGs may present antimicrobial activity, which is important to control the risk of contamination and infections (Fooladi, Hosseini, Hafezi, Hosseinnejad, & Nourani, ; Johari et al, ). We have demonstrated that our BG (BG90) has the marked ability to induce mineral matrix formation in vitro and to stimulate bone neoformation in vivo with a mild inflammatory process and similar outcomes to those of the autogenous bone graft control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional cell seeding process relies on the cell to adhere to the scaffold. In addition to the initial seeded cell quantity used in another study, which varied from 1.0 × 10 5 to 5.0 × 10 5 , the seeding efficiency was only 50% to 70% because most of the stem cells adhered only at the scaffold’s surfaces and easily fell off 3134 . Therefore, the actual seeding quantity in vivo is beyond prediction.…”
Section: Discussionmentioning
confidence: 99%